EVALUASI TAMAN LANSIA DI KOTA BANDUNG DENGAN KONSEP PLACE-KEEPING - Utama, Heidi Surya; Bella, Priyendiswara Agustina (Jurusan Arsitektur dan Perencanaan, 2025)
Thematic parks, including green open spaces (GOS), play a strategic role in enhancing urban residents' quality of life through their ecological, economic, social, and aesthetic functions. This study focuses on Taman Lansia (Elderly Park) in Bandung City, which, despite its high potential, currently experiences functional decline due to poor post-pandemic management. Using the place-keeping framework, this research aims to analyze the park's potential and challenges while providing sustainable management recommendations. Primary data were collected through field surveys, interviews, documentation, and questionnaires, while secondary data were obtained from literature sources. The analysis employed descriptive, crosstab, and comparative methods to evaluate the park's existing conditions based on the four main functions of GOS. The findings reveal significant challenges in Taman Lansia, such as deteriorated physical conditions, lack of community engagement, and insufficient elderly-friendly facilities. However, the park still holds substantial potential, especially with the integration of ecological and social functions. Recommendations include infrastructure improvements, provision of senior-friendly facilities, and strengthening collaborations with local communities to support the place-keeping concept. This study underscores the importance of sustainable management to enhance the functionality of urban GOS, particularly in Bandung City, as part of efforts to create a more comfortable, inclusive, and sustainable urban environment. Keywords: elderly park; green open space; place-keeping ; sustainable management ; thematic parks Abstrak Taman tematik, termasuk ruang terbuka hijau (RTH), memiliki peran strategis dalam meningkatkan kualitas hidup masyarakat perkotaan melalui fungsi ekologis, ekonomi, sosial, dan estetika. Penelitian ini berfokus pada Taman Lansia di Kota Bandung, yang meskipun memiliki potensi tinggi, saat ini mengalami penurunan fungsi akibat kurangnya pengelolaan pasca-pandemi. Berdasarkan kerangka place-keeping, penelitian ini bertujuan untuk menganalisis potensi dan permasalahan yang dihadapi taman ini serta memberikan rekomendasi pengelolaan yang berkelanjutan. Data primer dikumpulkan melalui survei lapangan, wawancara, dokumentasi, dan kuesioner, sementara data sekunder diperoleh dari berbagai sumber literatur. Analisis dilakukan menggunakan pendekatan deskriptif, crosstab, dan komparatif untuk mengevaluasi kondisi eksisting taman berdasarkan empat fungsi utama RTH. Hasil penelitian menunjukkan bahwa Taman Lansia memiliki berbagai tantangan, seperti kondisi fisik yang tidak layak, kurangnya aktivitas komunitas, serta minimnya fasilitas yang mendukung kebutuhan lansia. Namun, potensi taman ini tetap besar, terutama jika mempertimbangkan integrasi fungsi ekologis dan sosial. Rekomendasi meliputi perbaikan infrastruktur, penyediaan fasilitas lansia yang ramah, dan penguatan kolaborasi dengan komunitas setempat untuk mendukung konsep place-keeping. Penelitian ini menegaskan pentingnya pengelolaan berkelanjutan untuk meningkatkan fungsi RTH di perkotaan, khususnya di Kota Bandung, sebagai bagian dari upaya menciptakan kota yang lebih nyaman, inklusif, dan berkelanjutan.